Omitting vitamin and trace mineral premixes from diets during late finishing (190 to 250 lb) did not reduce growth performance, carcass leanness, or muscle quality - I H Kim; L L Burnham; Robert H Hines; M M Rantanen; I Mavromichalis; Joe D Hancock; Donald H Kropf; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1995)
Average daily gain; F/G; dressing percentage; tenth rib fat thickness; and depth, marbling, color, and firmness of the longissimus muscle were not influenced by omitting the vitamin and(or) trace mineral premixes from diets during late finishing (190 to 250 lb). Thus, our data suggest that the KSU vitamin and trace mineral premixes can be omitted during late finishing to reduce cost of gain without decreasing growth performance, carcass merit, or muscle quality.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Finishing; Vitamins; Minerals; Meat quality; Growth